Impact on postoperative complications of combined prehabilitation targeting co-existing smoking, malnutrition, obesity, alcohol drinking, and physical inactivity : a systematic review and meta-analysis of randomised trials - Lydom, Line N.; Jensen, Sofie Anne Marie S.; Lauridsen, Susanne V.; Rasmussen, Mette ; 0000-0003-2847-1544; Christensen, Robin; Joensen, Ulla N.; Rosenberg, Jacob; Tønnesen, Hanne (F1000Research, 2025)
Background: This study aimed to compare the effect on postoperative complications of combined prehabilitation targeting predefined co-existing risky SNAP factors with usual preoperative routines in surgical patients. Methods: This systematic review followed the PRISMA 2020 guideline and the protocol (CRD42022282611). Five databases were searched from inception to November 7, 2022 for randomised controlled trials on prehabilitation targeting ≥2 predefined risky lifestyles compared with usual preoperative routines. Risky lifestyles included Smoking, Nutrition (malnutrition and/or BMI>25), risky Alcohol intake, and Physical inactivity (SNAP). Primary outcome was postoperative complications ≤30 days. Cochrane’s risk-of-bias tool 2 was used and meta-analyses were conducted. GRADE was used to assess certainty of evidence. Results: The search resulted in 20,862 records. At full-text screening, only two (120 participants) of 24 identified trials on combined SNAP intervention had ≥2 predefined risk factors and were included. One (n=110) on intensive physical and brief nutritional intervention to frail patients with colorectal cancer resection reported complication rates of 45% in both groups (relative risk (RR) 1.00, 95% CI 0.66 to 1.51). The other study (n=10, subgroup) on intensive alcohol and smoking intervention in patients with bladder cancer undergoing radical cystectomy, reported complications in 3/7 vs 3/3 participants. The meta-analysis estimated a RR of 0.79 (95% CI 0.41 to 1.51, I 2 51%). Conclusion: Two small of the 24 trials on prehabilitation targeted co-existing and predefined risky SNAP factors and the effect on postoperative complications is very uncertain. Future prehabilitation research involving patient needs is warranted.
Publisher Copyright: Copyright: © 2025 Lydom LN et al.
Keywords: Lifestyle; Postoperative complications; Prehabilitation; Surgery